KURANGNYA DUKUNGAN ORANG TUA TERHADAP PENDIDIKAN ANAK DI DESA WATUDAKON KECAMATAN KESAMBEN KABUPATEN JOMBANG: The Lack of Parental Support for Children's Education in Watudakon Village, Kesamben District, Jombang Regency - Ramadhan Aji Sadewa; Ulfi Aminatuz Zahroh (Yayasan Al-Amin Qalbu, 2026)
This case study aims to describe the phenomenon of low parental support for children's education in Watudakon Village, Kesamben District, Jombang Regency. The main issues studied include lack of attention, supervision, learning motivation, and parental involvement in formal and non-formal educational activities. The study aimed to identify the factors causing low parental support, the forms of non-involvement that emerged, and their impact on children's learning processes. The research method used a qualitative case study approach through in-depth interviews and observations, with data analysis using the Miles & Huberman model. The results showed that low parental support was caused by time constraints, low education levels, economic factors, work fatigue, and a low perception of the importance of learning assistance. These findings align with previous studies on the role of socioeconomic status and parental perceptions of education (Nurwati & Listari, 2021; Ririk et al., 2023; Saputri et al., 2022; Suhaimi, 2020) . This research is expected to provide a factual picture of the state of children's education in rural areas and serve as a basis for recommendations for schools and village governments to improve collaboration with parents.